Nursing professionals and care in the care of oncological patients: practice, attitudes and knowledge the implementation of the humanization of care (Research, Society and Development, 2022)
Introduction: Cancer is a disease that affects various psycho-emotional aspects, due to the various changes that occur in its healing process, as well as feelings that need to be validated by both professionals and family members in general. It should be noted that nursing professionals are the ones who provide the most care. Because it is a disease that affects multiple aspects of life during the course, as well as its increasing number of diagnoses, for adequate and humanized care. Objective: To analyze the perception of nursing professionals about cancer patient care. Method: This is a study with a qualitative approach, of an integrative review type, whose database was the Virtual Health Library (VHL) using the Health Sciences Descriptors (DeCS): Nursing and oncology professionals and healthcare. Complete articles were selected, available in Portuguese, English and Spanish between 2011 and 2021. After applying the criteria, 11 articles emerged for content production. Results: The results presented in the study show the importance of the involvement of the nurse in the nursing care of the cancer patient, who must work in care activities, in addition to acting in their comprehensive care. Conclusion: When performing nursing care, it is extremely important that the patient is seen as a whole, carrying out the implementation of the nursing process and systematization of care, as well as the inclusion of family members or people close to the patient, in order to improve adherence to treatment and humanized care.